PENGGUNAAN EKSTENTION WAKTU DALAM ROLE ONLINE SYSTEM TICKETING RAHARJA (ROOSTER) SEBAGAI PENUNJANG PELAYANAN IDUHELP! - Meta Amalya Dewi; Dewi Immaniar; Siti Rahmawati (Universitas Raharja, 2014)
Rooster (Role Online System Ticketing Raharja) is an information service by using the “ online ticket” which is provided as an advanced container to accommodate questions from iDuHelp! Operators. In ROOSTER (Role Online System Ticketing Raharja) , iDuHelp! Operators acting as a customer that making an advance question which will be accepted by each staff based on their category.The submitted question must be in existed scope. But in ROOSTER service there are still some shortcomings that must be covered for research so it will conlclude many solution. Among many problems, the main problem is the lack of service time, so it can be concluded that the solution is to extend the service time when needed. With this system fix in rooster, iduhelp activity in ROOSTER will perform good.